Psychotherapy Expertise Should Mean Superior Outcomes and Demonstrable Improvement Over Time. (January 2017) - Goodyear, Rodney K.; Wampold, Bruce E.; Tracey, Terence J. G.; Lichtenberg, James W.
How the field understands psychotherapy expertise is important. It affects how we practice and how we prepare others for practice. As in our other work, we argue that the most meaningful definition of expertise must involve steady improvement over time to achieve superior performance on some meaningful measure, which typically is client outcome. We also argue that the best means by which a therapist can achieve this is through ongoing deliberate practice. We contrast our position with not only Hill, Spiegel, Hoffman, Kivlighan, and Gelso's preferred definition, in which they anchor expertise in therapist performance, but also with the various other possible definitions of expertise (e.g., therapist experience, therapist self-assessment of expertise) that they proffer as options.